Uterine Transplantation Using Living Donation: A Cross-sectional Study Assessing Perceptions, Acceptability, and Suitability. Issue 3 (18th February 2021) - Jones, Benjamin P.; Rajamanoharan, Abirami; Williams, Nicola J.; Vali, Saaliha; Saso, Srdjan; Mantrali, Ifigenia; Jalmbrant, Maria; Thum, Meen-Yau; Diaz-Garcia, Cesar; Ghaem-Maghami, Sadaf; Wilkinson, Stephen; Quiroga, Isabel; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: A uterine transplantation is a nonvital, quality-of-life–enhancing solid organ transplant. Given improvements in donor risk profile and the anticipated shortage of suitable deceased donors, nondirected donation could facilitate sustainability as uterine transplantation moves from research into the clinical realm. The aim of this article is to determine perceptions and identify motivations of potential nondirected living uterus donors and assess acceptability and suitability. Methods: A cross-sectional survey using an electronic questionnaire among women who have inquired about donating their uterus for uterine transplantation. Results: The majority of respondents "strongly agreed" or "agreed" that the most prevalent motivations to donate their uterus include helping someone carry and give birth to their own baby (n = 150; 99%), helping others (n = 147; 97%), and because they no longer need their womb (n = 147; 97%). After considering risks of uterus donation, the majority were still keen to donate their uterus (n = 144; 95%), but following a process of exclusion using donor selection criteria, less than a third (n = 42; 29%) were found to be suitable to proceed. Conclusions: This study demonstrates novel insight into the motivations of women who wish to donate their uterus and displays high levels of acceptability after consideration of the risks involved. Despite the physical risk and transient impact upon ability to undertake activities of daily living, women who donate their uterus expect to gain psychological and emotional benefits from enabling another woman to gestate and give birth to their own future children. However, currently used selection criteria reduce the number of potential donors significantly.